Case Report: Pulmonary color Doppler ultrasonography features of congenital tuberculosis in a preterm infant - Zhou, Di; Guo, Wanxu; Ma, Di; Zhang, Yunfeng (Frontiers in Pediatrics, 2025)
This study explores the color Doppler ultrasonography features of congenital tuberculosis in preterm infants through a detailed analysis of a case from February 2025, including clinical, NGS, and sonographic data. The findings identify specific vascular signatures that facilitate early diagnosis, offering a valuable reference for clinicians encountering similar cases. High-frequency probe ultrasonography was used to characterize pulmonary lesions and differentiate tuberculosis from bronchopulmonary dysplasia (BPD) and neonatal respiratory distress syndrome (NRDS). A male infant born at gestational age of 28 weeks (birth weight: 1,180 g) presented with respiratory distress and cyanosis (Apgar score: 7 at 1 min). Initial ultrasonography revealed multiple confluent B-lines in both lungs. At 60 days postpartum, ultrasonography showed thickened pleura, scattered subpleural consolidations, atelectasis in the lower lobes, and hyperechoic fragments moving with respiration. First-line anti-TB regimen, isoniazid, rifampin, and pyrazinamide were administered and serial monitoring via color Doppler ultrasound and chest CT demonstrated favorable disease control. Main take-away lessons: Pulmonary color Doppler ultrasonography, combined with clinical history, can aid in the diagnosis of congenital tuberculosis, and congenital TB should be considered in preterm infants with refractory pneumonia. Additionally, NGS is a valuable tool for rapid pathogen identification.